Interactions between climate warming and management actions determining bird community change in protected areas - Jonas, Leonie; Brommer, Jon E.; Jung, Martin; Baláž, Michal; Borg, John J.; Božič, Luka; Clausen, Preben; Derouaux, Antoine; Devos, Koen; Domșa, Cristian; Faragó, Sándor; Fitzgerald, Niamh; et al. (Elsevier BV, 2025)
Biodiversity is increasingly negatively affected by climate warming, making this issue a major conservation concern. Many bird species respond to warming temperatures by shifting distribution ranges, but these shifts often lag behind temperature changes. Protected areas (PAs) can facilitate such shifts, but a growing body of literature suggests that not all PAs facilitate climate warming responses equally, as realized management actions can differ. Here, we study waterbird community change as a response to climate warming in relation to targets of conservation projects implemented in Natura 2000 protected areas across the EU. We combine long-term waterbird survey data (i.e. International Waterbird Census) with data on conservation funded by the EU LIFE program, the main EU instrument for conservation. We used the community temperature index to measure thermal community changes over 28 years. We found community adjustment to climate warming lagged behind temperature. However, community change was twice as fast in sites were conservation was targeting wetland habitats compared with sites without habitat conservation. Targeting waterbirds directly did not lead to variation in community change compared with other types of species conservation. Our results imply that on the management level conservation targeting a community's habitat (rather than targeting the species group directly) is more likely to provide benefits for community adjustment to climate warming. This study demonstrates that management actions currently not targeting climate warming impacts on biodiversity, have the potential to support species responding to climate warming. However, conservation strategies need to be adapted to the challenges arising with climate warming.